Pengaruh Lingkungan Sekolah, Kesadaran Diri, Minat Belajar terhadap Kedisiplinan Belajar Siswa - Siti Khaira Sabila; Jean Elikal Marna (Jurnal Ecogen, 2023)
The objective of this research is to rephrase the goals of the study as follows:1) The Effect of school environment to the discipline of learning of SMP Negeri 1 Banuhampu, 2) The Effect of Self Awareness to  the discipline of learning of SMP Negeri 1 Banuhampu, 3) The  curiosity in Learning to the discipline of learning of SMP Negeri 1 Banuhampu.  This study employs a quantitative approach using the descriptive methodology. The all of students at SMP Negeri 1 Banuhampu constituted the study's population. This study's sample comprised students belonging to the VII and IX grades. In this study, a purposive sampling method was employed for sample selection.  The method utilized for analyzing the data involved multiple linear regression analysis techniques. The research instrument used a Questionnaire instrument with a Likert Scale.  Derived from the study's outcomes, it shows that the school environment, self-awareness and interest in learning simultaneously affect the learning discipline of students at SMP Negeri 1 Banuhampu.